Pharmaceutical nanotechnology: Antimicrobial peptides as potential new drugs against WHO list of critical, high, and medium priority bacteria - Roque-Borda, Cesar Augusto [UNESP]; Bento da Silva, Patricia; Rodrigues, Mosar Corrêa; Di Filippo, Leonardo Delello [UNESP]; Duarte, Jonatas L. [UNESP]; Chorilli, Marlus [UNESP]; Vicente, Eduardo Festozo [UNESP]; Garrido, Saulo Santesso [UNESP]; Rogério Pavan, Fernando [UNESP] (Elsevier, 2022)
Nanobiotechnology is a relatively unexplored area that has, nevertheless, shown relevant results in the fight against some diseases. Antimicrobial peptides (AMPs) are biomacromolecules with potential activity against multi/extensively drug-resistant bacteria, with a lower risk of generating bacterial resistance. They can be considered an excellent biotechnological alternative to conventional drugs. However, the application of several AMPs to biological systems is hampered by their poor stability and lifetime, inactivating them completely. Therefore, nanotechnology plays an important role in the development of new AMP-based drugs, protecting and carrying the bioactive to the target. This is the first review article on the different reported nanosystems using AMPs against bacteria listed on the WHO priority list. The current shortage of information implies a nanobiotechnological potential to obtain new drugs or repurpose drugs based on the AMP-drug synergistic effect.
Keywords: AMP; Carbapenem-resistant; Cephalosporin-resistant; Fluoroquinolone-resistant; Nanosystems; Nanotechnology